MEMAHAMI CITRA KOTA BERDASARKAN KOGNISI SPASIAL PENGAMAT (Studi Kasus: Pusat Kota Semarang) - Edi Purwanto; Edy Darmawan (Diponegoro University, 2013)
Understandingimage of the center Semarang city can be doneby knowing thespatial cognition of observers. Spatial cognition of observerdescribes howobserversobtain, organize, store, and recallinformationaboutthe location, distanceandarrangementwithinthecityenvironment. Spatial cognition of observers have the basic concepts Imageability and legibility. This research used adescriptiveapproachisto describeandinterpretthe object of observationin accordancewith what it is. The objective of this researchwas to determinethe level ofspatial cognitionability ofobserversin understanding image of the city. The results ofthe researchsuggests that theimage ofthe center of Semarang citycan be understoodifthecityhas the clear character, clear shape, clear pattern, clear structure, and elements ofclear signs, because it is necessary to provide an understanding of the oriented and identification for the observer.